Inpatient Omission of Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers Is Associated With Morbidity and Mortality in Coronavirus Disease 2019 - Oddy, Christopher (Clin Ther, 2021)
PURPOSE: Due to the affinity of severe acute respiratory syndrome coronavirus 2 for the human angiotensin-converting enzyme 2 (ACE2) receptor, use of ACE inhibitors and angiotensin receptor blockers (ARBs) has been a major concern for clinicians during the 2020 pandemic. Meta-analyses have affirmed that these agents do not worsen clinical outcomes in patients with severe acute respiratory syndrome coronavirus 2 infection. To date, only a limited number of studies have directly evaluated the safety of inpatient prescription of ACE inhibitors/ARBs during acute coronavirus disease 2019 (COVID-19) illness. METHODS: A retrospective cohort analysis was conducted to investigate the impact of inpatient provision of ACE inhibitors/ARBs on morbidity and mortality in patients admitted to the hospital with COVID-19. Relationships were explored by using linear and logistic regression. FINDINGS: A total of 612 adult patients met the inclusion criteria, of whom 151 (24.7%) patients were established on ACE inhibitors/ARBs. Despite correction for known confounders, discontinuation of ACE inhibitors/ARBs was highly predictive of worsened outcomes in COVID-19. The proportion of doses omitted in the hospital was significantly associated with increased mortality (OR, 9.59; 95% CI, 2.55–36.09; P < 0.001), maximum National Early Warning Score 2 (OR, 1.66; 95% CI, 1.27–2.17; P < 0.001), maximum oxygen requirements (OR, 3.00; 95% CI, 1.83–4.91; P < 0.001), and maximum C-reactive protein concentration (OR, 1.83; 95% CI, 1.06–3.17; P = 0.030). IMPLICATIONS: Our data show a strong association between missed ACE inhibitor/ARB doses with increased morbidity and mortality. The available evidence supports continuation of currently accepted practice surrounding ACE inhibitor/ARB therapy in acute illness, which is to limit drug omission to established acute contraindications, to actively monitor such decisions, and to restart therapy as soon as it is safe to do so. (Clin Ther. 2021;43:e97–e110) © 2021 Elsevier HS Journals, Inc.